Effect of Intradialytic Resistance Exercise on Restless Legs Syndrome Among Hemodialysis Patients: A Pilot Randomized Controlled Trial - Achmad Fauzi; Fatimah Ahmedy (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Restless legs syndrome (RLS) is common and burdensome among patients undergoing hemodialysis (HD). Intradialytic exercise provides a pragmatic opportunity for symptom management; however, evidence on resistance exercise during HD remains limited. Objective: This pilot study evaluated the effect of intradialytic resistance exercise on RLS severity in adults receiving maintenance HD. Methods: A two-arm, parallel-group pilot randomized controlled trial was conducted in two HD units (January–April 2025). Adults on thrice-weekly HD for ≥3 months with at least moderate RLS (IRLS ≥11) were randomized 1:1 to intradialytic resistance exercise (IRE) or usual care. The IRE group performed supervised elastic-band exercises during the first 2 hours of HD, three times weekly for 8 weeks. Outcomes were assessed at baseline, week 4, and week 8. The primary outcome was the International Restless Legs Syndrome Scale (IRLS) score, analyzed using mixed-effects models. Results: Forty-two participants were enrolled (IRE n=21; control n=21), with 90.5% completing the study. A significant group×time interaction was observed (p<0.001). At week 8, the IRE group demonstrated a clinically meaningful reduction in IRLS compared with controls (mean difference −8.4; 95% CI −11.7 to −5.0; Cohen’s d=1.11). Adherence was high and no serious adverse events occurred. Conclusions: An 8-week intradialytic resistance exercise program was feasible, safe, and effective in significantly reducing RLS severity among HD patients. Larger trials are warranted to confirm long-term benefits and implementation potential.